Respuesta :

Answer:

29

Step-by-step explanation:

f(x)=8(x−3)+13

f(5)= 8(5-3)+13

f(5) = 8(2) +13

f(5) = 16 +13

f(5)= 29

Hope this helps!

Please mark brainliest if you think I helped! Would really appreciate!

Answer:

Your correct answer is 29! Here is the step by step explanation!

Step-by-step explanation:

f(x)=8(x−3)+13

f(5)= 8(5-3)+13

f(5) = 8(2) +13

f(5) = 16 +13, wich means when you do this,

f(5)= 29

you get your answer of 29! Please mark brainliest! Hope it helped! Have a nice day!